Trách nhiệm xã hội doanh nghiệp và lòng trung thành của khách hàng tại thị trường bảo hiểm nhân thọ - Cao Thanh, Phong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Corporate social responsibility (CSR) is essential to an enterprise’s long-term development. Building customer loyalty through CSR activities is a new research aspect; however, this approach in the life insurance field has not been developed in the Vietnam context. The author proposes a research model with five components: CSR, Customer Satisfaction, Corporate Reputation, Customer Relationship, and Customer Loyalty. The quantitative method is implemented to test the research hypotheses with 137 life insurance customers in Can Tho City. The findings show that six of the seven initially proposed hypotheses have been accepted, confirming the positive relationship between CSR and Customer Loyalty. The author offers suggestions and recommendations for further study based on the research findings.